Stalinism and nazism : dictatorships in comparison - Kershaw, Ian 1943-; Lewin, Moshé, 1921- (Cambridge University Press, 1997)
The internationally distinguished contributors to this landmark volume represent a variety of approaches to the Nazi and Stalinist regimes. These far-reaching essays provide the raw materials towards a comparative analysis and offer the means to deepen and extend research in the field. The first section highlights similarities and differences in the leadership cults at the heart of the dictatorships. The second section moves to the 'war machines' engaged in the titanic clash of the regimes between 1941 and 1945. A final section surveys the shifting interpretations of successor societies as they have faced up to the legacy of the past. Combined, the essays presented here offer unique perspectives on the most violent and inhumane epoch in modern European history